A Critical Study on the History of Pandyan Dynasty: Exploring the Legacy of the Pandyan Dynasty (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Pandyan or Pandian dynasty was anancient Tamil dynasty, one ofthe three Tamil dynasties, the other two beingthe Chola and the Chera).The Pandya King, along with CheraKing and Chola King, together were called asThree Crowned Kings of Tamilakam.The dynasty ruled parts of South India from around 600 BCE (Early Pandyan Kingdom) to first half of17th century CE. They initially ruled their country PandyaNadu from Korkai, a seaport on the southernmost tip of the IndianPeninsula, and in later times moved to Madurai. Fishbeing their flag, Pandyas were experts in watermanagement, agriculture(mostly near river banks) and fisheries and they wereeminent sailors and sea traders too. Pandyan was well knownsince ancient times, with contacts, even diplomatic, reaching the RomanEmpire. The Pandyan empire was home to temples including Meenakshi Amman Temple in Madurai,and Nellaiappar Temple built on the bank of theriver Thamirabarani in Tirunelveli.The Pandya kings were called either Jatavarman or Maravarman Pandyan. Frombeing Jains in their early ages, they became Shaivaits after some centuries ofrule. Strabo statesthat an Indian king called Pandyan sent Augustus Caesar"presents and gifts of honour". The country of the Pandyas,Pandi Mandala, was described as Pandyan Mediterranea in thePeriplus and ModuraRegia Pandyan by Ptolemy.[6]